2014
DOI: 10.4103/0257-7941.150780
|View full text |Cite
|
Sign up to set email alerts
|

Anti-inflammatory activity of roots of Cichorium intybus due to its inhibitory effect on various cytokines and antioxidant activity

Abstract: Background:Cichorium intybus L. commonly known as chicory is one of the important medicinal plants commonly used in Ayurvedic system of medicine. It is commonly used for the treatment of diseases involving a khapa and pitta doshas. Traditionally, C. intybus is used for the treatment of inflammatory conditions, but there are only few in vitro studies reporting the anti-inflammatory activity of roots of chicory.Objective:Evaluation of anti-inflammatory activity of roots of chicory and mechanisms involved in it u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
16
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(18 citation statements)
references
References 20 publications
1
16
0
Order By: Relevance
“…In line with previous reports, the findings suggest that the anti-inflammatory effect of CSE might be linked with reduced expression of proinflammatory cytokines, such as TNF-α and NF-κB, in ET2D rats [ 39 ]. TNF-α is produced in the early stages of inflammation and controls the production of other cytokines.…”
Section: Discussionsupporting
confidence: 92%
“…In line with previous reports, the findings suggest that the anti-inflammatory effect of CSE might be linked with reduced expression of proinflammatory cytokines, such as TNF-α and NF-κB, in ET2D rats [ 39 ]. TNF-α is produced in the early stages of inflammation and controls the production of other cytokines.…”
Section: Discussionsupporting
confidence: 92%
“…Liver function was improved due to protective activity of antioxidants components in chicory extract, and it was shown that chicory decreased levels of MDA and increased GSH, antioxidant enzymes in (CCL 4 ) intoxicated rats [ 52 - 55 ]. Chicory cause elevation of intracellular antioxidant enzyme activities and decreased oxidative stress in tissues due to chicory extract enhance endogenous antioxidant defense status [ 49 , 56 ]. This hepatoprotection of chicory prevent liver damage, and no histopathological changes occur.…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, C. intybus linn supplementation decreased hepatic MDA, IL6 level and increased NQO1 enzyme activity in relation to TAA‐intoxicated group. Ahmed () and Rizvi et al () reported that C. intybus linn decreased MDA and IL6 level and increased antioxidant enzyme activities in diabetic rat brain and in vivo model of inflammation, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, C. intybus linn supplementation decreased hepatic MDA, IL6 level and increased NQO1 enzyme activity in relation to TAA-intoxicated group Ahmed (2009). andRizvi et al (2014) reported that C. intybus linn decreased MDA and IL6 level and increased antioxidant enzyme activities in diabetic rat brain and in vivo model of inflammation, respectively.AMPK maintains cellular energy homeostasis, regulates inflammatory response, and is important for macrophage's conversion from being pro-inflammatory to be anti-inflammatory during inflammation. Some AMPK activators as metformin were reported to have anti-fibrotic and anti-inflammatory effects in liver or in adipose tissues(Velagapudi, El-Bakoush, Lepiarz, Ogunrinade, & Olajide, 2017).…”
mentioning
confidence: 88%